2014
DOI: 10.1371/journal.pone.0095605
|View full text |Cite|
|
Sign up to set email alerts
|

Capsaicin Treatment Attenuates Cholangiocarcinoma Carcinogenesis

Abstract: Capsaicin, the most abundant pungent molecule produced by pepper plants, represents an important ingredient in spicy foods consumed throughout the world. Studies have shown that capsaicin can relieve inflammation and has anti-proliferative effects on various human malignancies. Cholangiocarcinoma (CC) is a cancer disease with rising incidence. The prognosis remains dismal with little advance in treatment. The aim of the present study is to explore the anti-tumor activity of capsaicin in cultured human CC cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…These effects were correlated with the down-regulation of phosphatidylinositol 3-kinase (PI3-K) and Akt [18]. Several other malignancies that have reported anti-migratory effects include cholangiocarcinoma and urothelial carcinoma [19,20]. Although the effects of PI3-K and Akt have not been investigated in our study, it is possible that modulation of this pathway could play a role in the anti-metastatic effects that we have found.…”
Section: Discussionmentioning
confidence: 52%
“…These effects were correlated with the down-regulation of phosphatidylinositol 3-kinase (PI3-K) and Akt [18]. Several other malignancies that have reported anti-migratory effects include cholangiocarcinoma and urothelial carcinoma [19,20]. Although the effects of PI3-K and Akt have not been investigated in our study, it is possible that modulation of this pathway could play a role in the anti-metastatic effects that we have found.…”
Section: Discussionmentioning
confidence: 52%
“…Hedgehog signaling components are overexpressed in iCCA [107][108][109], and it has been shown that GLI1 and GLI2 overexpression was associated with intrahepatic metastasis and poorer OS and DFS [108]. A role of Hedgehog signaling in EMT has been described in human CCA cells and CCA xenografted tumors by modulating E-cadherin expression [107] Consistently, inhibition of Hedgehog signaling by cyclopamine [107] or capsaicin [110] up-regulated E-cadherin expression [107] and impaired EMT in CCA [110]. Figure 2E) miRs are deeply involved in EMT regulation [14].…”
Section: Hedgehog Signaling Upon Hedgehog Ligand Binding Gpcr-like mentioning
confidence: 89%
“…In another study, proliferation, migration and invasion of human cholangiocarcinoma cells were all effectively inhibited by capsaicin, which was associated with regulating the Hedgehog signaling pathway [208]. …”
Section: Red Chili Pepper and Capsaicinmentioning
confidence: 99%